There’s A Stat for That: What to Do and When to Do it Bruce B Frey Sage Publications 2016 Reviewed by John Barnes - Barnes, John (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
This volume of 99 pages is different to other statistics books. Through an opening  quiz  you are informed which statistics process to use and why but not how, because most other books serving statistics do that